The Impact Of Influencer Marketing, Testimonials, and Promotional Discounts On The Purchase Intention Of Wardah Cosmetic Products : The Role Of Brand Image Mediation In Masamba - Ima; Edi Maszudi; Adi Firmanzah (International Journal of Management and Business Economics, 2026)
The development of digital marketing is driving changes in consumer behavior in determining cosmetic product purchasing decisions. This study aims to analyze the influence of influencer marketing, testimonials, and promotional discounts on Wardah product purchase intentions with brand image as a mediating variable in Masamba, North Luwu. The study used a quantitative approach with a survey method on 170 Wardah product user respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that testimonials (β = 0.218; p = 0.022), promotional discounts (β = 0.221; p = 0.017), and brand image (β = 0.394; p = 0.000) had a positive and significant effect on purchase intentions. In contrast, influencer marketing did not have a significant effect on purchase intentions (β = 0.086; p = 0.222). The mediation results indicate that brand image mediates the effect of promotional discounts on purchase intention (β = 0.112; p = 0.007), but does not mediate the effect of influencer marketing and testimonials. This study confirms that effective marketing strategies in non-urban areas emphasize testimonials and price promotions more than the use of influencers. The originality of this study lies in testing the integrated model in the context of non-urban consumers, which is still limited in the marketing literature.